Comparitive Study of Reamed vs Unreamed Interlocking Intra Medullary Nailing for Fracture Shaft of Tibia - Satyanarayana, S. V.; Mathivanan, N. (Sciencedomain International, 2021)
Tibia is the commonest bone to sustain open injury because of subcutaneous position. Treatment of open fractures requires simultaneous management of both skeletal and soft tissue injury. Intramedullary nailing with reaming is generally considered to be contraindicated for open fractures tibia, because it damages the endosteal blood supply which will lead to non-union, deep infection. However, recent studies with or without reaming in open fracture tibia shows no influence in healing of fracture. Purpose: To compare the clinical and radiological results of intramedullary interlocking nailing of open fractures of the tibial shaft after reaming versus unreamed medullary canal. The aim and objective is a comparative study on the technique, outcome and time taken for clinical and radiological union in either of the reamed or unreamed interlocking nailing in tibial shaft fractures. The operative technique, advantages and disadvantages, follow up, time taken for bony and radiological union and complications if any and overall functional outcome will be evaluated in patients. The follow up of patients will be done in the immediate post operative period and  subsequently  at periodic intervals both clinically and radiologically and the result so obtained will be compared.
Keywords: 3. Good health